Comparative analysis of food service satisfaction and nutritional adequacy between private hospitals and academic hospitals in patients with non-communicable diseases - Kartika Pibriyanti; Indahtul Mufidah; Lulu’ Luthfiya; Amal Fadholah; Ella Firdaus Sulistiyani; Banun Ma'rifah Fathsidni; Qotrunnadaa Fajr Rooiqoh; Nur Amala (AcTion: Aceh Nutrition Journal, 2024)
Nutritional services in hospitals aim to provide meals with high nutritional value, safety, appropriate quantity, quality, and satisfactory service. This study aimed to analyze and compare food service satisfaction and nutritional adequacy among patients with noncommunicable diseases (NCDs) in private and academic hospitals. The study was conducted at the UNS Hospital and YARSI Hospital from October to December. Employing a comparative cross-sectional study design, we included 50 patients with NCD, 25 general (private) hospitals, and 25 teaching hospitals. Satisfaction with food services was assessed using a validated food service satisfaction questionnaire, whereas nutritional adequacy was evaluated using the Comstock questionnaire. Nutrient intake data were processed using the NutriSurvey software. The Mann-Whitney U test was used for the statistical analysis. Our findings revealed significant differences in all food service satisfaction indicators (p<0,005), except for waitstaff friendliness (p=0,077). There were also significant differences in energy, fiber, macronutrient, and micronutrient adequacy levels, except for vitamin C intake, between patients in private and academic hospitals (p<0,005). In conclusion, the level of food services and nutritional adequacy differed significantly between private public and academic hospitals.